Learning Paragraph Writing In Indonesian Education For Students Of Sumbawa University Of Technology - Ramdani, Novita; Dzuljannah, Fadhilla; Tri Andini, Deka; Ayu Listari, Widya (Journal of Physical Education and Sports, 2025)
This journal discusses the writing and discussion of Indonesian paragraphs in the learning education of Sumbawa Technology University students. Paragraphs contain aspects of unity, the basic idea is expressed in topic sentences and developer ideas are expressed in developer sentences and these sentences are interconnected, then the aspect of developing basic ideas is expressed in topic sentences and developer ideas are expressed in explanatory or follow-up sentences, aspects of cohesion, namely the harmony of the relationship between ideas in the paragraph which also means the harmony of the relationship between sentences in the paragraph, aspects of cohesiveness, namely structural and lexical. the combination of sentences containing a main idea or main idea and several supporting ideas is the meaning of paragraphs. According to KBBI, a paragraph is part of a chapter in an essay, which usually contains one main idea and the writing begins with a new line. In expressing thoughts into sentences in scientific language, it should not be arbitrary and this makes it difficult for some people, because there is a difference between paragraphs and sentences, a sentence in writing does not stand alone, but is linked in a sentence.